Weekly Self-Scheduling, Forward Contracting, and Offering Strategy for a Producer - Garces, Lina P. [UNESP]; Conejo, Antonio J. (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Within a weekly market horizon, this paper considers a power producer that sells its energy both in the pool and through weekly forward contracts. The paper provides a methodology that allows the producer to derive the self-scheduling of its production units, to select weekly forward contracts, and to obtain the offering strategy for Monday's pool. The proposed technique is based on stochastic programming and allows the producer to maximize its expected profit while controlling the risk of profit variability. A comprehensive case study is used to illustrate the characteristics of the proposed methodology. Appropriate conclusions are finally drawn.
Keywords: Offering strategy; risk management; stochastic programming; weekly forward contracting; weekly self-scheduling